2016
DOI: 10.1097/mpg.0000000000001125
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Prognosis in Children and Adolescents With Autoimmune Hepatitis and Overlap Syndrome

Abstract: No statistically significant difference was observed between the groups in relation to prognosis and response to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 28 publications
5
21
1
Order By: Relevance
“…Also these adult patients had greater indication of orthotopic liver transplantation ( p = 0.009), but no differences in mortality. However, Rodrigues et al (27) reported statistically significant difference of prognosis and response to treatment was observed between the pediatric AIH and ASC groups.…”
Section: Discussionmentioning
confidence: 95%
“…Also these adult patients had greater indication of orthotopic liver transplantation ( p = 0.009), but no differences in mortality. However, Rodrigues et al (27) reported statistically significant difference of prognosis and response to treatment was observed between the pediatric AIH and ASC groups.…”
Section: Discussionmentioning
confidence: 95%
“…that, it is important separate PSC-AIH overlap with features of both diseases that is termed autoimmune sclerosing cholangitis (ASC) (2,4,5,15) . Separation between patients with isolated PSC and those with ASC is relevant because their prognosis is different due to response to immunosuppressants in ASC, unlike isolated PSC (8,12) . Differentiation between the two isn't always clear and progression of AIH to ASC has been documented in children in particular (8) .…”
Section: Discussionmentioning
confidence: 99%
“…The AHRQ score of each study was presented in Table 1 and Supplemental Digital Content (Appendix 3, http:// links.lww.com/MD/D462) (Table ), which illustrates the detailed AHRQ score. Ten studies [23][24][25][26][27][28][29][30][31][32] were of high quality and 15 studies [6,7,[33][34][35][36][37][38][39][40][41][42][43][44][45] were of moderate quality. There were no studies with low quality.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%